Fabrication of cellulose self-assemblies and high-strength ordered cellulose films. (6th March 2015) - Yuan, Zaiwu; Zhang, Jingjing; Jiang, Anning; Lv, Wenting; Wang, Yuewen; Geng, Hongjuan; Wang, Jin; Qin, Menghua
Highlights: Stable dispersions of cellulose self-assembly precursors are acquired. A variety of morphologies of cellulose self-assemblies are observed. High-strength ordered cellulose films are fabricated. Ordered cellulose films are potential for fabrication of high-strength functional cellulose materials. Abstract: Based on the formation of cellulose hydrogels in NaOH/urea aqueous solvent media, cellulose self-assembly precursor is acquired. It is proved that the water uptake capability of the cellulose hydrogels depends highly on the cross-link degree (CLD) of cellulose. With varying CLD and concentration of cellulose, a variety of morphologies of cellulose self-assemblies, including sheets with perfect morphology, high-aspect-ratio fibers, and disorganized segments and network, are formed through evaporation. Furthermore, cellulose films are fabricated by diecasting and evaporating the cellulose hydrogels, resulting in a 3D-ordered structure of closely stacking of cellulose sheets. The mechanical test indicates both tensile strength and flexibility of the cellulose films are greatly improved, which is attributed to the formation of the orderly stacking of cellulose sheets. The study is expected to lay an important foundation on the preparation of ordered and high-strength cellulose materials.